(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
With the release of La vita davanti a sé (Edoardo Ponti, 2020, Netflix) a number of interviews and documentaries have appeared on YouTube. Netflix-sponsored promotional materials and fan-circulated documentaries or interviews celebrate the Diva of the past and of the present, sustaining an ideal of resilience also supported by the flourishing silver economy of the last decades. The film, on the other hand, catches us by surprise, showing Loren’s elderly body in a graphic way and revealing the impossibility to hide its decadence. Focusing on the cultural continuities between today’s imaginary and that of the shapely diva of the ‘50s and ‘60s, this essay investigates Ponti-Loren’s attempt to find a new perspective on the Diva in light of her 86 years. A fundamental contradiction between an assenting old age and a retrograde approach comes to the fore.